New replacement name Kuznetsoviella (Ostracoda): a correction - Doweld, Alexander B. (Zootaxa, 2016)
Recently it was found (Doweld 2016) that the generic name Aenigma Kuznetsova (1957: 68; type species A. jucunda Kuznetsova, by original designation) of fossil Ostracoda from the Lower Cretaceous (Barremian) of Tegchaj, North-Eastern Azerbaijan, former USSR (Transcaucasia), is already preoccupied by a marine gastropod molluscan generic name Aenigma Newman (1836: 499), which is in active current use in zoology (Coleoptera: Carabidae), along with a few other known homonyms, Aenigma Amsel (1956: 288) [Lepidoptera], Aenigma Koch (in Martini & Chemnitz 1846: 1, unpaginated) [Mollusca], Aenigma Karsch (1878: 825) [Arachnida], Aenigma Strecker (1876: 122) [Lepidoptera]. Therefore, a new replacement name was proposed, Kuznetsovia Doweld (2016: 68). However, it was overlooked that this generic name is already preoccupied by Kuznetsovia Kammerer (2006: 269) [Arthropoda], escaped from Nomenclator Zoologicus and Zoobank. In this connection, to resolve unexpected homonymy with an arthropod generic name, in accordance with article 60 of the International Code of Zoological Nomenclature (1999), a new replacement name is proposed for the fossil Ostracoda genus: